1975
DOI: 10.1029/jb080i011p01381
|View full text |Cite
|
Sign up to set email alerts
|

Gravity field of the Kuril-Kamchatka Arc and its relation to the thermal regime of the lithosphere

Abstract: Five gravity anomaly profiles across the Sea of Okhotsk and the Kuril island arc and trench and two profiles from Fiji to Tonga are presented and studied. The four profiles across the Kuril arc are similar and differ from the profile extending off southern Kamchatka. The contributions to gravity anomalies from the crust and mantle are investigated by means of continuous seismic refraction measurements along tracks coincident with the gravity profiles. The mantle gravity anomalies computed from various density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In particular, the nonseismic Mussau Trench appears as an active trench with respect to gravity anomalies. As is shown elsewhere [Kogan, 1975], the gravity field near trenches is also significantly affected by density contrasts within the crust. Gravity anomalies due to the mantle can be estimated if the reliable seismic refraction data are available.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In particular, the nonseismic Mussau Trench appears as an active trench with respect to gravity anomalies. As is shown elsewhere [Kogan, 1975], the gravity field near trenches is also significantly affected by density contrasts within the crust. Gravity anomalies due to the mantle can be estimated if the reliable seismic refraction data are available.…”
Section: Discussionsupporting
confidence: 53%
“…It is almost absent in Bouguer anomalies, and hence the topography is out of isostatic balance. Unfortunately, deepseated sources give rise to large gravity effects in the area, and we refer to further discussion in the paper by Kogan [1975]. A marked positive free air anomaly of +300 mGal over the Western Samoa Platform implies that here the islands present an additional load supported by the lithosphere.…”
Section: E Hayes [Seementioning
confidence: 99%
See 1 more Smart Citation
“…Slow mantle velocities are also observed in surface wave studies [e.g., Kaila and Krishna , 1984; Ritzwoller and Levshin , 1998]. In addition, the Kamchatka back‐arc region is characterized by relatively low gravity, which has been modeled using a hot, low‐density mantle [ Kogan , 1975]. …”
Section: Thermal Structure Of Present‐day Back Arcs With No Significamentioning
confidence: 99%
“…Although our areas of study mainly involve continental regions, some oceanic belts are also found and allow the preceeding features to be compared with the oceanic data. Negative residual depth anomalies are typically found over the marginal seas (Sclater et al 1976;Karig, Anderson & Bidee 1978) and in particular over the eastern coast of Eurasia (Sclater, k t t e r & Dixon 1972;Kogan 1975), giving an illustration of the former feature.…”
Section: Comparison Between Observed and Theoretical Profilesmentioning
confidence: 99%